Initial Development of Mathematical Grit Scale for Senior High School - Gwenyth Lyn S Salming; Arabela O Hasan; Philvern Muyo; Retchelle P Sangco (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: Studies indicate that domain-specific grit scales have higher predictive power, yet no scale has been developed solely for mathematics. This study seeks to develop a reliable instrument for assessing mathematics-related grit of senior high school students. Methodology: A two-phase mixed-methods approach was employed, starting with in-depth interviews with Grade 12 students to develop the initial 46 items for the scale, which was then used in the quantitative phase through Exploratory Factor Analysis using JASP 0.19.3 Intel software. Main Findings: From the initial 46 items, the instrument was reduced to 32 items through Exploratory Factor Analysis with four extracted dimensions: Proactive Perseverance, Intrinsic Learning Drive, Perceived Mathematical Importance, and Extrinsic Learning Drive. The scale also showed high overall internal consistency. Novelty/Originality of this study: This study can be considered novel since the output, the Mathematical Grit Scale, would make a significant contribution to both psychology and education, particularly in the study of grit-related constructs. This would contribute to the ongoing research on the construct of grit in education.